Education between individual freedoms and social arrangements: the case of African graduates in Bulgaria (1960–1990) - Kachakova, Vesselina; Koleva, Svetla (Frontiers in Education, 2024)
The contradiction between the gains achieved in educational attainment in African countries and the persistence of individual and social vulnerability raises questions about the role of education in the development of both individual freedoms and social well-being. Searching for an interpretative key to this paradox, we have turned to the capability approach, developed by Amartya Sen, as offering a broad theoretical framework for the assessment and evaluation of individual freedoms and social arrangements.The research relies on archival documents from various socialist institutions in Bulgaria and 19 interviews with African graduates who studied in Bulgaria during the period 1960-1990. Viewed through the lens of Sen's capability approach, their educational and professional development reveals the spectrum of opportunities available to individuals as a result of different agreements in the field of education, as well as the deficits and limitations that affect individual and social well-being due to uncertain and changeable social arrangements at macro level.The intention of this research is a call for further development of the capability approach to better understand the dynamic relationships between individuals and social structures, the making of conversions and alternative combinations, and their influences on societal functioning. A possible direction for this development can be seen in Margaret Archer's concept of corporate agency and collective capacity. Collective agency is viewed as a possible bridge between individual agency and the social arrangements needed for effective societal change.